Clinical significance of unexpected antibody from IgG1 and IgG3 subtypes - LI Zhu; LI Danhong; LIU Zihao; ZHAO Jun; YANG Chengru; WANG Shoumei; DING Xiang (Zhongguo shuxue zazhi)
[Objective] To explore the clinical significance of the IgG1 and IgG3 subtypes of red blood cell unexpected antibodies. [Methods] The IgG1 and IgG3 typing tests were performed on the IgG type alloantibodies of Rh, Duffy and Kidd blood group systems detected in our hospital. Additionally, IgG1 and IgG3 titers were measured and monocyte monolayer assay was performed on 12 cases of anti-E to analyze the characteristics of different IgG subtypes of anti-E. [Results] Among the 115 cases of unexpected IgG antibodies, 81 cases of monospecific antibodies were predominantly IgG1 (58.02%, 47/81); 17 cases of mixed antibodies were predominantly IgG1+IgG3 (47.06%, 16/34). In monocyte monolayer assays, the phagocytic rate and antibody titer of IgG1 and IgG3 antibodies were positively correlated, while in IgG1+IgG3 complex antibodies, it was mainly associated with IgG3, with higher antibody titers correlating with higher phagocytic rates. When the anti-E titers were 32 for all, the IgG1+IgG3 complex had the highest phagocytosis rate, followed by IgG3 alone, and IgG1 alone had the lowest phagocytic rate. [Conclusion] Monospecific antibodies among unexpected antibodies are primarily IgG1, while mixed antibodies are mainly IgG1+IgG3. The results of MMA indicate that the immune response caused by the IgG1+IgG3 complex is more severe. Therefore, when antibodies like anti-E coexist with other antibodies, even if the titer is low, the immune response may still be severe, which should be taken seriously in clinical practice.